Learning How to Teach Chemistry with Technology: Pre-Service Teachers' Experiences with Integrating Technology into Their Learning and Teaching - Chittleborough, Gail (Journal of science teacher education, 2014)
The Australian Government initiative, Teaching Teachers for the Future (TTF), was a targeted response to improve the preparation of future teachers with integrating technology into their practice. This paper reports on TTF research involving 28 preservice teachers undertaking a chemistry curriculum studies unit that adopted a technological focus. For chemistry teaching the results showed that technological knowledge augmented the fundamental pedagogical knowledge necessary for teaching chemistry content. All the pre-service teachers demonstrated an understanding of the role of technology in teaching and learning and reported an increased skill level in a variety of technologies, many they had not used previously. Some students were sceptical about this learning when schools did not have technological resources available. This paper argues that teacher education courses should include technological skills that match those available in schools, as well as introduce new technologies to support a change in the culture of using technology in schools.